2015
DOI: 10.1007/s11999-015-4287-9
|View full text |Cite
|
Sign up to set email alerts
|

Network Meta-analysis: Users’ Guide for Surgeons: Part II - Certainty

Abstract: In the previous article (Network Meta-analysis: Users' Guide for Surgeons-Part I, Credibility), we presented an approach to evaluating the credibility or methodologic rigor of network meta-analyses (NMA), an innovative approach to simultaneously addressing the relative effectiveness of three or more treatment options for a given medical condition or disease state. In the second part of the Users' Guide for Surgeons, we discuss and demonstrate the application of criteria for determining the certainty in effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Over time, that series came to include dozens of articles, providing suggestions on how best to consume a wide variety of article types. We at Clinical Orthopaedics and Related Research 1 are proud to have published a pair of them recently [2,7]. Although the clinical examples in the original JAMA series are not musculoskeletal, those classic articles remain well worth a look.…”
Section: Tools For Thoughtful Readersmentioning
confidence: 99%
“…Over time, that series came to include dozens of articles, providing suggestions on how best to consume a wide variety of article types. We at Clinical Orthopaedics and Related Research 1 are proud to have published a pair of them recently [2,7]. Although the clinical examples in the original JAMA series are not musculoskeletal, those classic articles remain well worth a look.…”
Section: Tools For Thoughtful Readersmentioning
confidence: 99%
“…Still, they found no statistically significant differences in pooled effects between the two methods, although local infiltration was most likely to be superior in rank-order analysis. Despite the robust methodology of the study, the authors duly acknowledge limitations such as high heterogeneity, imprecision in the effect estimates and indirectness, all undermining confidence in the effect estimates and probability rankings [2,4,7]. The multitude of different interventions used in published randomized control trials is the major driver of the observed heterogeneity, which ranged from 66% to 97%, while complete lack of head-to-head comparisons creates indirectness.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…To minimize this likelihood, and to maximize the utility-and readers' enjoyment-of this important new approach to analyzing clinical evidence, we are pleased to offer a pair of ''User's Guides'' [2,6] to help readers understand not just this article but any future network meta-analyses that come along. Alongside these User's Guides, we also present a well-performed network meta-analysis on the care of a common fracture [7].…”
Section: S S Leopold MD (And) Clinical Orthopaedics and Relatedmentioning
confidence: 99%
“…But if this study design is new to you, I hope you will take advantage of this opportunity to learn how to read and enjoy network meta-analyses by taking advantage of the User's Guides [2,6]. This will be time well spent, both because they are good reading, and also because we expect to see many more studies using this design in the months and years to come.…”
Section: S S Leopold MD (And) Clinical Orthopaedics and Relatedmentioning
confidence: 99%